A 'navigator' model in emerging mental illness?. Issue 4 (24th July 2013) - Bieling, Peter J.; Madsen, Victoria; Zipursky, Robert B.
Abstract: Aim: While there is clearly much to be gained from ensuring that youth with emerging mental illness across a variety of psychiatric illnesses receive care that reduces symptoms and improves functioning, it is not at all clear how best to achieve these results within a health‐care system that has limited resources. Outside of the area of psychosis, there is little evidence to guide us around a model of care that might be effective, efficient and linked to existing mental health systems. Methods: We summarize the literature on early intervention (EI) in psychosis and derive five key lessons for transdiagnostic prevention. We then broadened our search to find clinical and systems models that shared challenges similar to those identified for EI, high levels of patient and family distress, need for rapid yet comprehensive diagnostic assessment and timely initiation of specific treatment. Results: Cancer navigators have numerous functions that appear to overlap with the key issues in transdiagnostic psychiatric EI. A navigation clinic with a separate identity, but clearly connected to specialized mental health facilities has the potential to speed assessment, diagnosis and treatment streaming. Navigators would be involved with youth and their family throughout different levels of care, making clinical decisions based on illness and functional status. Conclusions: In sum, the evidence from navigation services in cancer care offers the mental health field a progressive clinical model that might be an important guide for EI in youth.